Exploring of biological activity and diverse metabolites in hemp (Cannabis sativa) seed oil by GC/MS, GC-FID, and LC-HRMS chromatographies - İlhami Gulcin; Eda Mehtap Ozden; Muzaffer Mutlu; Ziba Mirzaee; Zeynebe Bingol; Ekrem Köksal; Saleh Alwasel; Ahmet C. Goren (SpringerOpen, 2024)
Abstract Background This study investigated the antidiabetic and antioxidant properties of hemp seed oil using various bioanalytical methods. Furthermore, this study determined the suppressive properties of hemp seed oil on α-amylase, acetylcholinesterase and carbonic anhydrase II that purified by the sepharose-4B-L-Tyrosine-sulfanilamide affinity chromatoghraphy, all of which are related to different metabolic diseases. Moreover, the phenolic concentration in the essential oil was quantified through LC-HRMS chromatography. Thirteen distinct phenolic compounds were detected in hemp seed oil. Additionally, both the chemical components and quantity of essential oils within hemp seed oil were assessed through GC-FID and GC/MS analyses. Results The predominant essential oils in hemp seed oil included linoleoyl chloride (34.62%), linoleic acid (33.21%), and 2-4-di-tert-butylphenol (5.79%). Hemp seed oil's ability to scavenge radicals was studied through the use of 2,2'-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) and 1,1-diphenyl-2-picrylhydrazil bioanalytical radical scavenging methods. The results unveiled its potent radical-scavenging properties, with an 46.20 μg/mL for 2,2'-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) radicals and IC50 of 9.76 μg/mL for 1,1-diphenyl-2-picrylhydrazil radicals. The investigation also extended to explore the reducing capabilities of Fe3+-2,4,6-tri(2-pyridyl)-S-triazine, copper (Cu2+), and iron (Fe3+). Hemp seed oil demonstrated notable inhibitory effect against α-amylase (IC50: 545.66 μg/mL), achethylcholinesterase (IC50: 28.00 μg/mL), and carbonic anhydrase II (IC50: 322.62 μg/mL). Conclusions This interdisciplinary research will prove valuable and set the stage for future investigations into the antioxidant characteristics and enzyme inhibition patterns of plants and plants oils that hold medical and industrial significance.